Investigation of the Emergency Physicians’ Exposure to Violence and Forensic Events - Kaya, Erhan; Tanır, Ferdi (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study is to determine the exposure of the emergency department physicians to violence and forensic events and related factors. Materials and Methods: The population of this cross-sectional study was 248 emergency service physicians working at 31 different health institutions in Adana city center. Between 01 July and 31 December 2016, 202 emergency department physicians were interviewed face-to-face. Data collection tools were; the sociodemographic knowledge of the doctors, the history of violence and their approach to forensic events. Frequency analysis and Chi Square test were used for data evaluation. Results: The mean age of the participants was 38.3±9.6 years and mean working time in emergency departments was 8.9±7,7 years and 75.7% of the emergency physicians in our study were male. The rate of exposure to violence during the working life was 88.1%. The most common types of violence were verbal violence with 88.1% and physical violence with 30.7%. It was determined that physicians were mostly violated by patients and their relatives, also it was determined that half of the physicians went to court at least once during their professional life due to medical practices. Statistically significant relationship was found between physicians being violent and being plaintiff (p<0,05). It was stated that 20.8% of the doctors had a forensic investigation and 85.6% were concerned about the malpractice. Conclusion: Emergency physicians, who are faced with violence and forensic events very often and undertake great medical and legal responsibilities, can feel anxious and lonely. Legal sanctions on violence against...